Bridge to Transplantation With Long‐Term Mechanical Assist Devices in Adults With Transposition of the Great Arteries1. Issue 1 (28th October 2018) - Michel, Eriberto; Orozco Hernandez, Erik; Enter, Daniel; Monge, Michael; Nakano, Jota; Rich, Jonathan; Anderson, Allen; Backer, Carl; McCarthy, Patrick; Pham, Duc
Abstract: Prior to the widespread adoption of the arterial switch operation, patients with transposition of the great arteries (TGA) commonly underwent atrial switch operation (Mustard or Senning). It is not uncommon for these patients to progress to end stage heart failure and increasingly ventricular assist devices (VADs) are used to support these patients as a bridge to transplantation, though there is limited experience with this worldwide. A retrospective review of our institution's VAD database was undertaken and revealed seven adult patients with a history of TGA and subsequent systemic ventricular failure were implanted with a VAD: four of whom received the VAD as a bridge to transplantation (BTT) at the time of implantation, two who were initially designated as destination therapy secondary to severe pulmonary hypertension, and one who was designated as destination therapy secondary to a high risk of life‐threatening non‐compliance. Seven patient cases who received a VAD for severe systemic ventricular failure were included in this study. The mean age of the patients was 40 years and the majority of patients were male (6/7, 85%). Five of the patients (71.4%) had previously undergone an atrial switch operation and all of these were Mustard procedures. Two of the seven patients (28.5%) had congenitally corrected transposition of the great arteries (CC‐TGA). Two of the seven patients (28.5%) had supra‐systemic pulmonary pressures before VAD implantation and were designated as destination therapy (DT). One of these patients was later designated as BTT as an improvement in his pulmonary vascular resistance was observed, and subsequently underwent heart transplantation. Because of anatomic considerations, four of the patients (57%) underwent redo‐sternotomy with outflow cannula anastomosis to the ascending aorta, one patient underwent VAD implantation via a left subcostal incision with anastomosis of the outflow graft to the descending thoracic aorta, and two patients (28.5%) underwent VAD implantation via a left thoracotomy and anastomosis of the outflow cannula to the descending thoracic aorta. Six of the seven patients had a HeartWare HVAD VAD implanted; one received a Thoratec Heartmate II VAD. Two patients underwent VAD explant and orthotopic heart transplant, 222 days and 444 days after VAD implant, respectively. One patient died on postoperative day 17 after complications from recurrent VAD thrombosis despite multiple pump exchanges. Four patients remain on VAD support, three of these patients are awaiting transplantation at last follow‐up (mean days on support, 513 days). Bridge to transplantation with a durable VAD is technically feasible and relatively safe in patients with TGA. Multiple redo‐sternotomies can be avoided with a left posterior thoracotomy approach and outflow graft anastomosis to the descending thoracic aorta after careful anatomic considerations.